2022
DOI: 10.3390/cells11172723
|View full text |Cite
|
Sign up to set email alerts
|

A Cysteine Residue within the Kinase Domain of Zap70 Regulates Lck Activity and Proximal TCR Signaling

Abstract: Alterations in both the expression and function of the non-receptor tyrosine kinase Zap70 are associated with numerous human diseases including immunodeficiency, autoimmunity, and leukemia. Zap70 propagates the TCR signal by phosphorylating two important adaptor molecules, LAT and SLP76, which orchestrate the assembly of the signaling complex, leading to the activation of PLCγ1 and further downstream pathways. These events are crucial to drive T-cell development and T-cell activation. Recently, it has been pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In addition, it has been proposed that cysteine 564, located in the kinase domain of ZAP70, is palmitoylated, and that a Cys-to-Arg mutation preventing palmitoylation blocks TCR signaling and T-cell activation [ 123 ]. However, it has been recently shown that, although such a mutation prevents palmitoylation, a ZAP70 mutant in which cysteine 564 is replaced by a non-palmitoylable alanine residue is able to transduce TCR signaling, and even enhances the activity of Lck and increases its proximity to the TCR [ 124 ]. Therefore, C564 seems to be another relevant component in the regulation of proximal TCR signaling by ZAP70 kinase.…”
Section: Keeping Zap70 In Checkmentioning
confidence: 99%
“…In addition, it has been proposed that cysteine 564, located in the kinase domain of ZAP70, is palmitoylated, and that a Cys-to-Arg mutation preventing palmitoylation blocks TCR signaling and T-cell activation [ 123 ]. However, it has been recently shown that, although such a mutation prevents palmitoylation, a ZAP70 mutant in which cysteine 564 is replaced by a non-palmitoylable alanine residue is able to transduce TCR signaling, and even enhances the activity of Lck and increases its proximity to the TCR [ 124 ]. Therefore, C564 seems to be another relevant component in the regulation of proximal TCR signaling by ZAP70 kinase.…”
Section: Keeping Zap70 In Checkmentioning
confidence: 99%
“…This change enhanced the pairing efficiency and stability of the exogenous α and β chains, reduced the occurrence of mismatch, increased the expression of exogenous TCR on the cell surface, and enhanced the antigen-specific response. Studies have shown that this strategy can reduce the autoimmune pathological reactions caused by TCR mismatch [ 528 ].…”
Section: Introductionmentioning
confidence: 99%